Current issues of the Japanese mobile phone market caused by smartphones - Sobee Shinohara; Yuji Akematsu; Hiroyuki Morikawa; Masatsugu Tsuji (International Telecommunications Society (ITS), 2013)
The mobile market has been transforming quickly all over the world particularly caused by the diffusion of smartphones, and this study attempts to examine the effect of smartphones to the Japanese mobile phone market. Japan has so far the well-developed 3G mobile phone in terms of not only the diffusion rate but also affluent functionality to consumers' use; Japanese 3G mobile phones are not only for voice calls, but it can send e-mails, view homepages, download music (Full Uta), purchase goods and services (Osaifu keitai, wallet phone) and more. Based on authors' paper on 3G mobile in Japan (Akematsu, Shinohara, and Tsuji, 2012), this study examines policy issues of the mobile phone market caused by the emergence and growth of smartphones, which were firstly introduced in 2008 to the Japanese market. This paper focuses on the impacts of smartphones to competition between iPhone and Android-powered mobiles, and policy such as MNP. Based on results obtained, brief policy recommendations for further promoting competition in the mobile market are presented.
Keywords: 330; Smartphone; iPhone; Android; feature phone; 3G mobile phone; panel data analysis